1988
DOI: 10.1111/j.1095-8339.1988.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oils of Ocimum urticifolium (Lamiaceae) chemotypes grown in Rwanda

Abstract: NTEZURUBANZA, L., SCHEFFER, J. J. C. & SVENDSEN, A. B., 1988. Composition of the essential oils of Ocimum urticifolium (Lamiaceae) chemotypes grown in Rwanda. Leaves and flowers of 48 specimen of Ocimum urticifolium (synonym: O. suave), Lamiaceae, were collected in different parts of Rwanda. The volatile components of each specimen were isolated by hydrodistillation under standardized conditions, and the 48 essential oils analysed by thin‐layer chromatography. This preliminary analysis showed six different oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The in vivo studies by the same researchers also showed a protective effect of eugenol at doses of 5 and 25 mg/kg against CCI 4 induced hepatotoxicity. The methanolic extract of leaves of Ocimum suave (Lamiaceae), which contains eugenol as a major constituent [19], has shown gastric cytoprotective and anti-ulcer effects in experimental Wistar rats [20]. Eugenol pre-treatment (10-100 mg/kg) reduces both the number of gastric ulcers and the gravity of lesions induced by ulcerogenic agents like platelet activating factor and ethanol [21].…”
mentioning
confidence: 99%
“…The in vivo studies by the same researchers also showed a protective effect of eugenol at doses of 5 and 25 mg/kg against CCI 4 induced hepatotoxicity. The methanolic extract of leaves of Ocimum suave (Lamiaceae), which contains eugenol as a major constituent [19], has shown gastric cytoprotective and anti-ulcer effects in experimental Wistar rats [20]. Eugenol pre-treatment (10-100 mg/kg) reduces both the number of gastric ulcers and the gravity of lesions induced by ulcerogenic agents like platelet activating factor and ethanol [21].…”
mentioning
confidence: 99%